PRE-SERVICE TEACHERS’ TEACHING SKILLS, ENGLISH PROFICIENCY, INTERCULTURAL SENSITIVITY, EXPOSURE TO FOREIGN CULTURE ACROSS L2 ENVIRONMENTS - Susilo, Susilo (International Journal of Language Education, 2019)
This was a survey study involving 156 pre-service teachers taken from three local universities in Indonesia, investigating whether or not different L2 learning environment of English teacher education affect the NNES pre-service teachers’ teaching skills, intercultural sensitivity, exposure to foreign culture, and English proficiency. The data were collected through observation scaling checklist, and 2) questionnaire. Descriptive analysis and a series of one-way ANOVA were used to analyze the data. The results showed that: 1) the effect of L2 learning environments on teaching skills was not significant F (2) = 2.831., p = 0.062; 2) the effect of L2 learning environments on intercultural sensitivity was not significant F (2) = 4.991, p = 0.008; 3) the effect of L2 learning environments on exposure to foreign culture was not significant F (2) = 1.577, p = 0.210., and 4) the effect of L2 learning environments on English proficiency was significant F (2) = 56.153, p = 0.000.